Effect of Soya and Potato on Shelf-life of Chicken Meat Emulsion under Refrigerated Condition - Kumari, Sushma; Singh, J.N.; Kumar, Sanjay; Soni , Kumari (Journal of Meat Science, 2015)
A study was conducted to determine the shelf-life of chicken meat emulsions prepared from spent hen meat and preserved under refrigerated (4 ± 1°C) condition so that fresh chicken nuggets could be prepared as per need. Three different types of emulsions were prepared viz. T1 as control (100 % chicken meat), T2 (80 % chicken meat+ 20 % soya) and T3 (80 % chicken meat+ 20 % boiled potato) and were analyzed for various physico-chemical and microbial parameters during storage under refrigerated condition (4 ± 1°C) for one week. The pH and TBA value showed increasing trend in all the emulsions but significant (p>0.01) increase was noticed from 5th day onwards. Total plate count, psychrophilic count and yeasts & moulds count increased significantly (p>0.01) as the days advanced, with higher counts in extended emulsions as compared to control. Coliform count also increased significantly (p>0.01) but indicated higher count in control than extended emulsion.
Keywords: Emulsion; Extender; Minced soy; Boiled potato